1992
DOI: 10.1002/food.19920360213
|View full text |Cite
|
Sign up to set email alerts
|

Subacute oral toxicity study of benzyl isothiocyanate in rats

Abstract: The subacute toxicity of benzyl isothiocyanate (BITC) was investigated in male rats given oral doses of 0, 50, 100 and 200 mg/kg body weight/day for 4 weeks. Body weight gain and food consumption were decreased with increasing doses of BITC. Haematological changes of toxicological relevance were observed in the highest dose group. BITC administration resulted in increased serum cholesterol level in all treatment groups and decreased serum triglycerides level at 200 mg/kg. Renal dysfunction was indicated by red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…On the other hand, AITC was previously reported to induce renal microscopic changes such as dilatation of distal tubules and increased desquamation in rats given a dose of 20 mg/kg body weight/day by gavage for 6 weeks (Lewerenz et al, 1988). T-Cho was also found to be decreased with a dose-dependence in females given HRE, whereas among ITCs, BITC was reported to increase serum cholesterol levels (Lewerenz et al, 1992). Although the composition of the test substance and the procedure for administration were different, the cause of these discrepancies may be due to some other factors.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, AITC was previously reported to induce renal microscopic changes such as dilatation of distal tubules and increased desquamation in rats given a dose of 20 mg/kg body weight/day by gavage for 6 weeks (Lewerenz et al, 1988). T-Cho was also found to be decreased with a dose-dependence in females given HRE, whereas among ITCs, BITC was reported to increase serum cholesterol levels (Lewerenz et al, 1992). Although the composition of the test substance and the procedure for administration were different, the cause of these discrepancies may be due to some other factors.…”
Section: Discussionmentioning
confidence: 90%
“…Warin et al [20] reported previously that the administration of BITC at 1 and 3 mmol/kg for 25 weeks did not induce weight loss or any other adverse effect in the MMTV-neu mice. However, several studies reported that various ITCs cause toxicity in the kidney and liver when administered at relatively high doses (20-200 mg/kg body weight/day) [33][34][35][36][37]. In order to determine whether BITC causes toxicity in the kidney at the doses used in this study, we measured the serum levels of creatinine, an indicator of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…BITC, a potential chemopreventive agent (Wattenberg, 1983) has been shown to be toxic to some cells/tissues in vitro and in vivo. Male rats exposed to BITC (orally) showed significant histological changes in some organs and tissues (Lewerenz, 1992). Rats exposed to BITC (0.1% in the diet) were also reported to show prominent characteristics of toxicity like single cell necrosis, cytoplasmic vacuolation, erosion and haemorrhage of the urinary bladder (Akagi et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Lewerenz et al (1992) reported that oral exposure of male rats to high concentrations of BITC caused peritonitis, adhesions between the diaphragm, stomach, spleen, pancreas and liver. It is thus envisaged that at the toxic level that will be needed to kill and expel intestinal worms in vivo, BITC may also cause impairment of intestinal motility and functions.…”
Section: Discussionmentioning
confidence: 98%